Sub-clinical borderline personality disorder symptoms as predictor of suicidality and non-suicidal self-injury in young Pakistani females - Gull Zareen; Farzana Ashraf (Journal of the Pakistan Medical Association, 2020)
Abstract The aim of this study was to determine if suicidal and non-suicidal self-injury can be predicted by the symptoms of Borderline Personality Disorder (BPD) and if non-suicidal self-injury predicts suicidality in young adult females. In this cross-sectional study, 150 undergraduate females (mean age 20.47±3.17) were conveniently sampled and assessed on McLean Screening Instrument for Borderline Personality Disorder, Suicidal Behaviour Questionnaire-Revised, and the Inventory of Statements about Self-injury. Borderline Personality features significantly predicted suicidal ideation and behaviour (?=.383, p<.001) and non-suicidal self-injury (?.282, p<.01). Likewise, non-suicidal self-injury was positively associated with suicidality (r =.330, p<.01). Even sub-threshold BPD features in a non-clinical population may be predictive of suicidal and non-suicidal self-injury. Future research should be based on the management and interventional strategies for tested constructs. Further, screening measures need to be introduced to better detect population at risk of subclinical BPD, suicidal ideation and self-injury. Keywords: Suicidal, Self-injury, Continuous...